YOUTH-LED INTERFAITH ADVOCACY AND COUNTER-CONSERVATISM: THE CASE OF PELITA IN WEST SUMATRA, INDONESIA - Zulfadli; Ilham Pramadia; Muhammad Wafi Muhadzib; Kurnia Aznar Putra; Arival Aryadi; Rayhan Febran Seprapdi (Penamas, 2025)
This study aims to examine the involvement of the Interfaith Youth Community (Pemuda Lintas Agama, or PELITA) in Padang as an active movement engaged in social advocacy against Islamic conservatism in West Sumatra. This youth community carries out various interfaith advocacy activities and peace campaigns and facilitates spaces for social encounters to promote tolerance and respond to incidents of intolerance and discrimination in the region. The research uses a qualitative method with an interfaith advocacy approach. The findings reveal that the active role of youth as initiators and drivers of counter-narratives to religious conservatism not only helps to curb the growing dominance of conservative discourse in public spaces but also attracts other young people to engage in issues of diversity. Through its wide range of activities, youth engagement in diversity-related issues proves to be highly significant and strategic in constructing a counter-narrative to religious conservatism, particularly in the face of passive (permissive) tendencies among the majority group. This research offers recommendations and key lessons in encouraging active youth involvement in interfaith advocacy as a means to promote tolerance and inspire similar movements across other regions in Indonesia